Peircean semiotics: Building possible paths for understanding the appropariation and resignification of national symbols (Research, Society and Development, 2022)
This theoretical essay aims to reflect on the appropriation and resignification of national symbols in the light of Peircean semiotics. For this, we seek to elucidate about the theoretical field of Peirce's American semiotics and the resignification of national symbols with regard to the History of the Present Time and the political conjuncture of Brazil, having as a cut the civil/military coup of 1964, the redemocratization process, the impeachment of Fernando Collor de Mello, the 2013 protests and the current political period. It is observed that, throughout history, although several movements have used national symbols, currently, this appropriation is restricted to the extreme right, in such a way that its use is directly associated with this aspect. It is understood that national symbols relate to the feeling of belonging, the idea of national unity and political pluralism. Thus, it is argued that the appropriation of the country's national symbols belongs to all Brazilians, without distinction of political-party or ideological affiliation.